Strand-specific RNA-Seq transcriptome analysis of genotypes with and without low-phosphorus tolerance provides novel insights into phosphorus-use efficiency in maize. Issue 1 (December 2016) - Du, Qingguo; Wang, Kai; Xu, Cheng; Zou, Cheng; Xie, Chuanxiao; Xu, Yunbi; Li, Wen-Xue
Abstract Background Phosphorus (P) stress is a global problem in maize production. Although macro/microarray technologies have greatly increased our general knowledge of maize responses to P stress, a greater understanding of the diversity of responses in maize genotypes is still needed. Results In this study, we first evaluated the tolerance to low P of 560 accessions under field conditions, and selected the low P-tolerant line CCM454 and the low P-sensitive line 31778 for further research. We then generated 24 strand-specific RNA libraries from shoots and roots of CCM454 and 31778 that had been subjected to P stress for 2 and 8 days. The P deficiency-responsive genes common to CCM454 and 31778 were involved in various metabolic processes, including acid phosphatase (APase) activity. Determination of root-secretory APase activities showed that the induction of APase by P stress occurred much earlier in CCM454 than that in 31778. Gene Ontology analysis of differentially expressed genes (DEGs) and CAT/POD activities between CCM454 and 31778 under P-sufficient and -deficient conditions demonstrated that CCM454 has a greater ability to eliminate reactive oxygen species (ROS) than 31778. In addition, 16 miRNAs in roots and 12 miRNAs in shoots, including miRNA399s, were identified as DEGs between CCM454 and 31778. Conclusions The results indicate that the tolerance to low P of CCM454 is mainly due to the rapid responsiveness to P stress and efficient elimination of ROS. Our findings increase the understanding of the molecular events involved in the diversity of responses to P stress among maize accessions.